2020
DOI: 10.2514/1.j058501
|View full text |Cite
|
Sign up to set email alerts
|

Control-Oriented Model Reduction for Minimizing Transient Energy Growth in Shear Flows

Abstract: A linear non-modal mechanism for transient amplification of perturbation energy is known to trigger sub-critical transition to turbulence in many shear flows. Feedback control strategies for minimizing this transient energy growth can be formulated as convex optimization problems based on linear matrix inequalities. Unfortunately, solving the requisite linear matrix inequality problem can be computationally prohibitive within the context of high-dimensional fluid flows.In this work, we investigate the utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Control will alter the perturbation dynamics, and so the optimal disturbance for the controlled flow will differ from that of the uncontrolled flow, in general. 25 This point has been emphasized in recent studies [26][27][28] aiming to evaluate the overall performance of feedback controllers.…”
Section: Introductionmentioning
confidence: 99%
“…Control will alter the perturbation dynamics, and so the optimal disturbance for the controlled flow will differ from that of the uncontrolled flow, in general. 25 This point has been emphasized in recent studies [26][27][28] aiming to evaluate the overall performance of feedback controllers.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we overcome the issue with computational complexity by taking advantage of control-oriented reduced-order models (ROM), similar to those described in [15]. Once we have computed the stabilizing SOF controller gain F 0 using the ROM, this can be used to initialize the Anderson-Moore algorithm (see Algorithm 1) for yielding an SOF-LQR control solution.…”
Section: Appendix A: Stabilizing Static Output Feedback Controllermentioning
confidence: 99%
“…Further, modal analysis techniques can be tailored to and leveraged for feedback flow control synthesis. Within the context of channel flow control, numerous model reduction strategies have been developed around modal decomposition techniques, e.g., global mode truncation [81] and input-output modeling [82][83][84]. Recent efforts have demonstrated that a model reduction approach needs to be selected and tailored carefully with respect to the control objective [83,84].…”
Section: A Linearly Stable Laminar Channel Flowmentioning
confidence: 99%
“…Within the context of channel flow control, numerous model reduction strategies have been developed around modal decomposition techniques, e.g., global mode truncation [81] and input-output modeling [82][83][84]. Recent efforts have demonstrated that a model reduction approach needs to be selected and tailored carefully with respect to the control objective [83,84]. For example, within the context of transient energy growth reduction, the performance of feedback controllers designed on reduced-order models (ROMs) can be quite sensitive to the parameters used in generating the underlying ROMs [83,84].…”
Section: A Linearly Stable Laminar Channel Flowmentioning
confidence: 99%
See 1 more Smart Citation